Triggering Receptor Expressed on Myeloid Cells-1 Inhibitor Targeted to Endothelium Decreases Cell Activation - Gibot, Sébastien; Jolly, Lucie; Lemarié, Jérémie; Carrasco, Kevin; Derive, Marc; Boufenzer, Amir (Frontiers in Immunology, 2019)
TREM-1 (Triggering Receptor Expressed on Myeloid cells-1) is an immunoreceptor expressed on neutrophils, monocytes/macrophages, and endothelial cells. It amplifies the inflammatory response driven by Toll-Like Receptors engagement. The pharmacological inhibition of TREM-1 confers protection in several pre-clinical models of acute inflammation. In this study, we aimed to investigate the role of TREM-1 in endothelial cells using a sneaking ligand construct (SLC) inhibiting TREM-1 in the endothelium. The SLC was made of 3 modules: an E-selectin targeting domain, a Pseudomonas aeruginosa exotoxin A translocation domain, and a 7 aa peptide (LSKSLVF) that contains the interaction site between TREM-1 and its adaptor protein DAP-12. SLC peptide was effectively picked up by endothelial cells following LPS stimulation. It decreased LPS induced TREM-1 up-regulation and cell activation, neutrophils extravasation, and improved survival during experimental peritonitis in mice. We reported that a targeted endothelial TREM-1 inhibition is able to dampen cell activation and to confer protection during septic shock in mice. The use of such cell-specific, ligand- independent, TREM-1 inhibitors deserve further investigations during acute or chronic inflammatory disorders.